Paediatric one-day admission: why and is it necessary? - Jing Zhan Lock; Zi Xean Khoo; Jen Heng Pek (Singapore Medical Journal)
Introduction: Paediatric patients admitted to the inpatient units from the emergency department (ED) are increasing, but the mean length of stay has fallen significantly. We aimed to determine the reasons behind paediatric one-day admissions in Singapore and to assess their necessity. Methods: A retrospective study involving paediatric patients who were admitted from a general ED of an adult tertiary hospital to a paediatric tertiary hospital between 1 August 2018 and 30 April 2020. One-day admission was defined as an inpatient stay of less than 24 h from the time of admission to discharge. An unnecessary admission was defined as one with no diagnostic test ordered, intravenous medication administered, therapeutic procedure performed or specialty review made in the inpatient unit. Data were captured in a standardised form and analysed. Results: There were 13,944 paediatric attendances — 1,160 (8.3%) paediatric patients were admitted. Among these, 481 (41.4%) were one-day admissions. Upper respiratory tract infection (62, 12.9%), gastroenteritis (60, 12.5%) and head injury (52, 10.8%) were the three most common conditions. The three most common reasons for ED admissions were inpatient treatment (203, 42.2%), inpatient monitoring (185, 38.5%) and inpatient diagnostic investigations (32, 12.3%). Ninety-six (20.0%) one-day admissions were unnecessary. Conclusion: Paediatric one-day admissions present an opportunity to develop and implement interventions targeted at the healthcare system, the ED, the paediatric patient and their caregiver, in order to safely slow down and perhaps reverse the trend of increased hospital admissions.